Association between antecedent statin use and decreased mortality in hospitalized patients with COVID-19 - Gupta, Aakriti; Madhavan, Mahesh V.; Poterucha, Timothy J.; DeFilippis, Ersilia M.; Hennessey, Jessica A.; Redfors, Bjorn; Eckhardt, Christina; Bikdeli, Behnood; Platt, Jonathan; Nalbandian, Ani; Elias, Pierre; Cummings, Matthew J.; et al. (Nature communications, 2021)
The coronavirus disease 2019 (COVID-19) can result in a hyperinflammatory state, leading to acute respiratory distress syndrome (ARDS), myocardial injury, and thrombotic complications, among other sequelae. Statins, which are known to have anti-inflammatory and antithrombotic properties, have been studied in the setting of other viral infections, but their benefit has not been assessed in COVID-19. This is a retrospective analysis of patients admitted with COVID-19 from February 1 st through May 12 th , 2020 with study period ending on June 11 th , 2020. Antecedent statin use was assessed using medication information available in the electronic medical record. We constructed a multivariable logistic regression model to predict the propensity of receiving statins, adjusting for baseline sociodemographic and clinical characteristics, and outpatient medications. The primary endpoint includes in-hospital mortality within 30 days. A total of 2626 patients were admitted during the study period, of whom 951 (36.2%) were antecedent statin users. Among 1296 patients (648 statin users, 648 non-statin users) identified with 1:1 propensity-score matching, statin use is significantly associated with lower odds of the primary endpoint in the propensity-matched cohort (OR 0.47, 95% CI 0.36–0.62, p < 0.001). We conclude that antecedent statin use in patients hospitalized with COVID-19 is associated with lower inpatient mortality. Statins, which have anti-inflammatory and antithrombotic properties, could have effects in COVID-19 patients. Here, the authors find in a retrospective analysis of patients hospitalized with COVID-19 that antecedent statin use is associated with lower inpatient mortality.